Revision of the bee genus Thectochlora Moure (Hymenoptera, Apidae, Halictinae) - Gonçalves, Rodrigo B.; Melo, Gabriel A.r. (Zootaxa, 2006)
The genus Thectochlora Moure has been treated as containing only a single species. Based on morphological characters, five species are here recognized: T. alaris (Vachal, 1904), the type-species of Thectochlora; T. basiatra (Strand, 1910) new combination, previously placed in Pseudaugochlora; and three new species, T. brachycera new species (Brazil and Guiana), T. hamata new species (Brazil and Uruguay) and T. mixta new species (Brazil). A male syntype of Augochloropsis (Pseudaugochloropsis) basiatra Strand, 1910, from Paraguay (Villa Morra), is here designated lectotype in order to stabilize the taxonomy of the group. The species of Thectochlora are distinguished based mainly in the males; females of T. alaris and T. basiatra were considered indistinguishable. An identification key, cladistic analysis, maps of geographic records and illustrations are presented.